2020
DOI: 10.1099/jgv.0.001353
|View full text |Cite
|
Sign up to set email alerts
|

Virus infection induces resistance to Pseudomonas syringae and to drought in both compatible and incompatible bacteria–host interactions, which are compromised under conditions of elevated temperature and CO2 levels

Abstract: Virus infection induces resistance to Pseudomonas syringae and to drought in both compatible and incompatible bacteria-host interactions, which are compromised under conditions of elevated temperature and CO2 levels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…2008 ; Hily et al. 2016 ; Aguilar et al. 2020 ) and on virus evolution towards mutualism under conditions of abiotic stress for the host ( González et al.…”
Section: Discussionmentioning
confidence: 99%
“…2008 ; Hily et al. 2016 ; Aguilar et al. 2020 ) and on virus evolution towards mutualism under conditions of abiotic stress for the host ( González et al.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has become increasingly evident that plant–virus interactions are not limited to a simple reaction to pathogen infection and that they can shift from antagonist to mutualistic or beneficial responses to environmental changes 12 , 13 . Viruses can increase the tolerance of plants to drought and cold stress 14 , high soil temperatures 15 , and bacterial pathogens 16 , 17 . V. vinifera cv ‘Bosco’ infected by GRSPaV showed greater tolerance to water stress than virus-free plants 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, it was shown that expression of P25 by PPV led to an increase of PPV virulence and to a concomitant drought-tolerant phenotype in parental N. benthamiana plants [ 18 , 30 ]. The expression of the SA-responsive gene pathogenesis-related protein 1 ( PR-1 ), as well as transcript levels of the defense-related genes Hin1 and Hsr203j, were increased at much higher levels in PPV-P25-infected plants compared with plants infected with PPV [ 31 ]. In addition, metabolic and hormonal data further supported an altered physiological status in plants infected with PPV-P25 of more amplitude than the one triggered by PPV infection [ 18 ].…”
Section: Discussionmentioning
confidence: 99%